SEISMIC MICROZONATION FOR BANDA ACEH CITY PLANNING - Johar, Foziah; Majid, M. Rafee; Jaffar, Abdul Razak; Yahya, Adi Safyan (PLANNING MALAYSIA, 2013)
Of all natural disasters of the twentieth century, earthquakes caused the largest amount of losses. Although the number of earthquakes remains fairly unchanged, the loss of properties and human lives in recent periods has increased manifolds due to increasing concentration of human population and urbanisation in earthquake-prone areas. Recent improvement in documentations and computational facilities, however, allows for the preparation of seismic microzonation maps of such areas for urban planning and earthquake mitigation purposes. This paper discusses the development of seismic microzonation maps for Banda Aceh which lies close to the Sumatra Subduction Zone and the Sumatran Transform Faults, making the city extremely vulnerable to earthquake hazards. The development of the maps employs Geographic Information Systems (GIS) techniques that make use of several layers of parameters influencing earthquake hazards such as seismological data, faults, tsunami, etc. and site characteristic data such as soil type, groundwater distribution and depth, geological and geophysical data. The seismic microzonation maps incorporate various seismic hazard maps including ground shaking hazard map, liquefaction susceptibility hazard map, landslide potential hazard map, surface faulting hazard map and tsunami hazard map. The final composite map identifies zones with various degrees of hazards which will enable planners to avert hazardous locations during site selection processes, thus reducing losses.